PROPOSED APPLICATION OF SIX SIGMA AND KAIZEN METHODS TO IMPROVE THE QUALITY OF THE BUS IN THE PUTTY PROCESS AT PT.MEKAR ARMADA JAYA (Science and Technology (SciTech), 2022)
PT. Mekar Armada Jaya is a company engaged in the automotive body industry. One of the products it produces is the touristo, magneto, SHD/HDD, and double-decker bus fleets. In the production process, PT. Mekar Armada Jaya has experienced problems with the Bus Putty Shop, namely the high level of defect. Based on the company's actual Defect per unit (DPU) from January to December 2021, namely the coarse putty fuel cap, coarse putty front cowl, and porous putty LH hull. The number of top defect internal putty bus for one year was 235 of the total number of buses produced, 315 of them with the type of defect, namely 102 units of coarse putty fuel cap, 73 units of coarse putty front cowl, and 60 units of LH porous putty on the hull. Based on the above problems, they can be solved using the six sigma and kaizen methods. The method used in this study to solve the problem at the Bus Putty Shop in PT. Mekar Armada Jaya is known as DMAIC (Define, Measure, Analyze, Improve, Control). diagram SIPOC (Supplier-Input-Process-Output-Customer), CTQ (critical to quality), diagram pareto, diagram sebab-akibat (fishbone), dan usulan perbaikan 5W+1H, Five M-Checklist (man, milleu, method, machine, and material) dan Five Step Plan (seiri, seiton, seiketsu, dan shitsuke). Based on the results of data processing at PT Mekar Armada Jaya's Bus Putty Shop, researchers can conduct the following analyses and investigations: With the sigma value conversion iteration, it can be seen that the production of buses, especially in the Bus Putty Shop section at PT. Mekar Armada Jaya, has an average sigma level of 0.85 with a defect per million opportunities (DPMO) of 742,154 in a million production. viewed in a percentage Pareto chart, the most dominant defect percentages are Coarse Putty Fuel Cover by 43%, Coarse Putty Front Cowl by 31%, and Hull LH Porous Putty by 26%. The results of the improvement will enable the company to make improvements in improving the quality of buses and reducing top internal defects on the Putty Shop Bus using the 5W + 1H method, namely repairing top internal defects. To facilitate the scrubbing of the fuel gap lite area, a trial replacement of the fuel leaf connection was carried out using M5 X 15 X 1.25 Bolts and an action plan process was carried out with kaizen, namely the Five M-Checklist (man, milleu, method, machine, and material) dan Five Step Plan (seiri, seiton, seiketsu, dan shitsuke).   Keywords: Quality, Putty Shop Bus, Six Sigma, 5W+1H, Kaizen